2013
DOI: 10.1038/cddis.2013.119
|View full text |Cite
|
Sign up to set email alerts
|

The Myb-p300-CREB axis modulates intestine homeostasis, radiosensitivity and tumorigenesis

Abstract: The gastrointestinal (GI) epithelium is constantly renewing, depending upon the intestinal stem cells (ISC) regulated by a spectrum of transcription factors (TFs), including Myb. We noted previously in mice with a p300 mutation (plt6) within the Myb-interaction-domain phenocopied Myb hypomorphic mutant mice with regard to thrombopoiesis, and here, changes in GI homeostasis. p300 is a transcriptional coactivator for many TFs, most prominently cyclic-AMP response element-binding protein (CREB), and also Myb. Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 56 publications
2
25
1
Order By: Relevance
“…Although we did not confirm any stimulatory effect of quinaldic acid on HT-29 cell proliferation, previous work reported that active p-CREB is elevated in colorectal cancer cells, which suggests that CREB may have a role in gastrointestinal malignancy (Sampurno et al, 2013). Moreover, CREB overexpression may lead to drug resistance of colon cancer cells as it is required for the expression of MRP2 (multidrug resistant protein 2) (Sampurno et al, 2013).…”
Section: Discussioncontrasting
confidence: 82%
“…Although we did not confirm any stimulatory effect of quinaldic acid on HT-29 cell proliferation, previous work reported that active p-CREB is elevated in colorectal cancer cells, which suggests that CREB may have a role in gastrointestinal malignancy (Sampurno et al, 2013). Moreover, CREB overexpression may lead to drug resistance of colon cancer cells as it is required for the expression of MRP2 (multidrug resistant protein 2) (Sampurno et al, 2013).…”
Section: Discussioncontrasting
confidence: 82%
“…CREB has been found in phosphorylated states in gastrointestinal malignancy; however, its role in intestinal homeostasis remains unclear. 72 In our experimental models cAMP elevation precedes CREB phosphorylation, as would be expected. However, the initial peak of pCREB precedes that of pPKA, suggesting an alternative mechanism of CREB activation.…”
Section: Discussionsupporting
confidence: 69%
“…Recently, Sampurno et al (2013) demonstrated that in mouse colorectal cancer (CRC) cells and adenomas, pCREB is elevated and is required for the increased expression of Mrp2. This was tentatively associated with increased chemoresistance to frontline drugs such as oxaliplatin, 5-fluorouracil, and camptothecin.…”
Section: Discussionmentioning
confidence: 99%